Socioeconomic, bio-demographic and health/behavioral determinants of neonatal mortality in Nigeria: a multilevel analysis of 2013 demographic and health survey - Adewuyi, E.; Zhao, Yun; Lamichhane, R. (Medip Academy, 2016)
International Journal of Contemporary Pediatrics (IJCP) is an open access, international, peer-reviewed journal that publishes original research work in all areas of pediatric research. The journal's full text is available online at http://www.ijpediatrics.com. The journal allows free access to its contents. International Journal of Contemporary Pediatrics is dedicated to publishing research in all aspects of health of infants, children, and adolescents. The journal has a broad coverage of relevant topics in pediatrics: General Pediatrics, Neonatal-Perinatal Medicine, Adolescent Medicine, Infectious Diseases, Vaccines, Allergy and Immunology, Gastroenterology, Cardiology, Critical Care Medicine, Developmental-Behavioral Medicine, Endocrinology, Hematology-Oncology, Nephrology, Neurology, Emergency Medicine, Pulmonology, Rheumatology and Genetics. International Journal of Contemporary Pediatrics (IJCP) is one of the fastest communication journals and articles are published online within short time after acceptance of manuscripts. The types of articles accepted include original research articles, review articles, insightful editorials, case reports, short communications, correspondence, images in pediatrics, clinical problem solving, perspectives and pediatric medicine. It is published every two months and available in print and online version. International Journal of Contemporary Pediatrics (IJCP) complies with the uniform requirements for manuscripts submitted to biomedical journals, issued by the International Committee for Medical Journal Editors.